Comparative efficacy of short-pulsed intense pulsed light and pulsed dye laser to treat rosacea. (4th July 2019) - Kim, Bo Young; Moon, Hye-Rim; Ryu, Hwa Jung
ABSTRACT: Background : Laser and light-based therapies have often been used successfully to treat rosacea. Recently, short-pulsed intense pulsed light (IPL) that emitted pulse durations down to 0.5 ms was found to be effective for rosacea treatment. Objective : This study evaluated the efficacy of short-pulsed IPL in the treatment of rosacea compared with pulsed dye laser (PDL) using same pulse duration and fluence. Materials and Methods : Nine patients with rosacea were enrolled in a randomized, split-face trial. Each treatment consisted of four sessions at three-week intervals and followed up until three weeks after the last treatment. Efficacy was assessed by erythema, melanin index, physician's subjective evaluation, and patient's satisfaction. Results : The mean change in erythema index was −4.93 ± 1.59 for the short-pulsed IPL group and −4.27 ± 1.23 for the PDL group. The mean change in melanin index was −2.52 ± 2.45 for the short-pulsed IPL group and −1.95 ± 1.41 for the PDL group. There was no significant difference in either melanin or erythema index between short-pulsed IPL and PDL treatments, and there were no noticeable adverse events. Conclusions : There was no significant difference between PDL and short-pulsed IPL treatment using the same energies and pulse. Both PDL and short-pulsed IPL were satisfactory and safe for rosacea treatment.